2008
DOI: 10.4012/dmj.27.172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water on Bonding of One-bottle Self-etching Adhesives

Abstract: This study evaluated the effect of water on dentin substrate bonding of one-bottle self-etching adhesives. Dentin substrates were divided into two groups: wet and dry dentin. Wet dentin is the normal substrate for bond testing whereas dry dentin was dehydrated in a desiccator for 24 hours. Bonded dehydrated teeth were then divided into two subgroups: stored in water or in desiccator for 24 hours. Microtensile bond strength of resin to dentin was measured using three one-bottle self-etching adhesives. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…32 Water trees are water canals at the adhesive interface created by the highly osmolarity of the adhesive solution generating nanoleakage. [11][12][13] In vivo studies are in agreement with the current results, showing good results of 1-SEAs for marginal integrity. 1,21,22,24 With regards to postoperative sensitivity, one restoration bonded with Clearfil S3 Bond, one with Single Bond 2. and one with Optibond All-in-One showed postoperative sensitivity at the one-year recall.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…32 Water trees are water canals at the adhesive interface created by the highly osmolarity of the adhesive solution generating nanoleakage. [11][12][13] In vivo studies are in agreement with the current results, showing good results of 1-SEAs for marginal integrity. 1,21,22,24 With regards to postoperative sensitivity, one restoration bonded with Clearfil S3 Bond, one with Single Bond 2. and one with Optibond All-in-One showed postoperative sensitivity at the one-year recall.…”
Section: Discussionsupporting
confidence: 80%
“…9,10 Self-etching adhesive systems are also subject to hydrolysis caused by the high permeability of the adhesive layer (osmosis), which generates nanoleakage at the adhesive interface. [11][12][13] Some clinical studies have showed good clinical performance of two-step self-etching systems. [14][15][16][17][18] Recently, one-step self-etching adhesive systems (1-SEAs) were introduced as the seventh generation of etching systems, which combine acid conditioning, primer, and adhesive in one bottle.…”
Section: Introductionmentioning
confidence: 99%
“…Further, shear bond strength test revealed that with #600 polishing, self-adhesive resin cements failed to exhibit acceptable bond strengths. Minute amounts of water left in the smear layer and intrinsic water in enamel most probably led to limited ionization of the demineralizing monomers, which was one more indication that resin cements or adhesives are able to absorb water from their bonding surfaces through diffusion 26) . As for self-etching adhesive systems, their In (c, h), similar morphology was seen as BR and G-Bond contained the same adhesive monomer 4-MET.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, HEMA-free one-step self-etch adhesive systems have recently been introduced with the expectation of reducing water sorption and increasing the long-term stability of the mechanical properties. Ultrastructural observation of the adhesive interface of one-step self-etch adhesives has shown nanoleakage in the adhesive layer as well as in the hybrid layer 20,21) . Additionally, HEMA-free adhesives express water-tree nanoleakage formation above the resin-dentin interface due to phase separation of adhesive components and osmotic water infiltration as a result of water remaining on the dentin substrate or being transported from the dentinal tubules 15,22,23) .…”
Section: Introductionmentioning
confidence: 99%